Determinação de estatinas em plasma humano empregando cromatografia líquida com colunas de meio de acesso restrito - Vinicius Freire Fagundes (2013)
This study presents the preparation of a Restricted Access Media (RAM) column with immobilized bovine serum albumin (BSA) by crosslinking with glutaraldehyde. The homemade RAM column was compared with commercial alkyl-diol silica (ADS) RAM column regarding human plasma proteins exclusion using the total protein determination method of BRADFORD. These columns were also evaluated and compared in terms of the quality and capacity retention of micromolecules, determining the retention factor and asymmetry of nine acidic (ketoprofen, diclofenac and pravastatin), neutral (bromazepam, omeprazole and theophylline) or basic drugs (mebendazole, propranolol and trimethoprim), changing the mobile phase pH. It was also developed chromatographic methods for statins determination, lipid-lowering drugs, in human plasma using RAM columns as extracting phases in an automated column-switching system. The chromatographic conditions such as mobile phase flow-rate and composition, turning valve time, oven temperature and detection wavelength in the ultraviolet range were optimized for both modes of column-switching chromatography elution: backflush and foreflush. The method employing the backflush mode, whose total time of the analytical run was about a half of the time required in foreflush mode, was then selected for the determination of lovastatin, pravastatin, rosuvastatin and simvastatin in human plasma using atorvastatin as internal standard. This method was fully validated according to RDC 27 of ANVISA. The RAM-BSA column had simple preparation and, as well as ADS-RAM commercial, has shown capacity for excluding human plasma proteins and presented retention suitable for the different compounds evaluated. Thereby, the RAM-BSA column is a viable alternative for replacing the commercial column. The developed and validated bioanalytical method proved to be simple, rapid, precise and accurate for simultaneous determination of statins in human plasma in the range 125-876 ngmL-1 for lovastatin, simvastatin and rosuvastatin and 500-2000 ngmL-1 for pravastatin.